Investigating Teacher’s Questioning Strategies and Students’ Responses in Learning English at Junior High School 18 Mataram - Amrullah, Amrullah; Kamalia, Ima; Elmiana, Dewi Satria; Lail, Husnul (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
The study aims to investigate the types of questioning strategies that the English teacher used during the classroom interaction at Junior High School 18 Mataram and to discover how students respond to the teachers’ questions. The research method used was a descriptive qualitative and the participants were an extensive-experienced English teacher and 18 students of grade eigth. The result of this study showed that the types of questions used by the English teacher were 7 procedural questions, 9 convergent questions, and 2 divergent questions, and the result of the students’ responses were the lower-order thinking students' responses in the Understanding section (C2) and the higher-order thinking students' responses in the Analysis section (C4). In conclusion, while the teacher at SMPN 18 Mataram effectively employed questioning to manage the classroom and check comprehension, the limited use of higher-order questions constrained the potential for deeper cognitive and linguistic engagement. Future instructional practices should aim to diversify questioning strategies to better support the development of both language proficiency and critical thinking in junior high school English learners.